Smoky Mountain lullabies [compact disc] - Duncan, Craig; Duncan, Craig (Green Hill instrumental collection., 2021)
A homegrown, acoustic collection of gentle lullabies featuring traditional instruments of the Smoky Mountains including hammered dulcimer, fiddle, autoharp, guitar, and more.